Efficiency Of Hydrogen Production From Sea Water Using The Electrolysis Process With Solar Energy Photovoltaic Systems - Fadhli, Fadhli; Hakim, Lukman; Setiawan, Adi; Dewi, Rozanna; Zulnazri, Zulnazri; Daud, Muhammad; Sari, Ratna (Politeknik Negeri Lhokseumawe, 2024)
Hydrogen is a future alternative energy source, offering environmental friendliness and renewable properties that can potentially replace fossil fuels. Despite the potential, its synthesis typically requires high energy and costs, posing a constraint on mass production due to low efficiency. Therefore, this study aims to develop hydrogen production technology from seawater using the electrolysis process with solar energy from photovoltaic systems as energy source. The experiments were carried out with different voltages of 10, 15, 20, and 25 volts, using electrode materials made of titanium in mesh and plate shapes. Seawater served as the electrolyte, and it was supplemented with 0.1 molNaOH and 0.1 mol H2SO4. The results showed that the applied voltage had a positive correlation with hydrogen production rate, while the electrolysis process time had no significant effect. In addition, the use of NaOH catalyst with mesh-shaped titanium electrode could yield efficiency of hydrogen production flow rate of 2.06% or 52 ml/minute. This outcome was better compared to the electrolysis of seawater electrolyte with and without H2SO4 catalyst, which yielded values of 1.84% or 30.1 ml/minute and 1.42% or 28.9 ml/minute, respectively.